Assessment of fall armyworm tolerant maize hybrids for sustainable maize production in sub-Saharan Africa - Amegbor, Isaac Kodzo; Adu, Gloria Boakyewaa; Nelimor, Charles; Boddupalli, Prasanna; Beyene, Yoseph; Chivasa, Walter; Gethi, James Gichuru; Togola, Abou; Jamal-Deen, Abdulai; Adogoba, Desmond; Nboyine, Jerry Asalma; Kusi, Francis; et al. (Springer, 2025)
Fall armyworm (Spodoptera frugiperda (J.E. Smith)) has become a significant pest to maize production, causing huge yield losses in sub-Saharan Africa. This study evaluated three non-Bt maize hybrids with tolerance to fall armyworm (FAW) along with a commercial hybrid check for yield and agronomic performance under natural FAW infestation and chemical control conditions in both on-station and on-farm trials. Significant differences were observed among the hybrids with the FAW tolerant hybrids showing reduced leaf and ear damage compared to the commercial hybrid. These hybrids also exhibited high grain yield performance, outyielding the commercial check by 197-252%. Mean grain yield under FAW infestation ranged from 6009.88 to 7117.30 kg ha-1 without chemical control, and even higher (8441.24 kg ha-1) under limited chemical control. Stepwise multiple regression analyses identified ear aspect, husk cover and ear damage as key traits accounting for 98% of the total variation in grain yield under FAW infestation. Participatory variety selection showed high farmer preference for these hybrids. The availability of these hybrids to farmers promises to enhance food security, reduce the environmental impact of insecticides, alleviate cost burdens on farmers, and increase household income.